Potential of Chemolitotrophic Bacteria From Gold Mining Area in Sulfur Oxidation Process - Fitriyani, Nur Lu'lu; Irianto, Agus; Pramono, Hendro (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Gold in nature is covered by rocks which contain sulfide minerals such as pyrite, chalcopyrite, arsenopyrite, and others sulfide minerals. Chemolithotrophic bacteria have the ability to oxidize the sulfur compounds and can be used in the process of releasing gold from carrier rocks which contain sulfide minerals. This research aimed to explore and identify the chemolithotrophic bacteria from gold mining areas as well as determine their potential for sulfur oxidation. The methods used in this study were exploring the potential of bacteria in sulfur oxidation and describing the variety of bacteria that were isolated from gold mining areas by 16s rRNA identification. The results showed that there were six isolates from isolation with Starkey solid medium, i.e. Bl-1, B1-2, B1-3, B1-4, B1-5 and B1-6 that were similar to Paenibacillus sp., Enterobacter ludwigiis train E8-13, uncultured Burkholderia sp., Uncultured bacterium clone N4.5, Bacillus subtilis strain CICC 10023, and Bacterium enrichment culture clone 02 respectively. The B1-3 isolate showed the highest increase of sulfate compound in the medium (8.04 % at 649.55 ppm). This indigenous bacteria will be able to be used to release gold from rock which contains sulfide minerals and reduce the use of hazardous chemicals commonly used in gold mining.